A 6-b 12-GSamples - Jaesik Lee
This paper presents a 6-b 12-GSample/s track-and-hold amplifier (THA) fabricated in an InP-InGaAs-InP double heterojunction bipolar transistor (DHBT) technology. The THA is intended for the front end of a high-speed analog-to-digital converter in a digital-based electronic polarization-mode dispersion compensation circuit for a 10-Gb/s optical receiver. With a high-speed switched emitter follower and clocked track-to-hold transition operation, it shows the signal bandwidth over 14 GHz and features a total harmonic distortion (THD) compatible with 6-b operation with input frequency of 6 GHz and a sampling frequency of 12 GHz. The THD increases better than -23 dB with a 12-GHz input signal of 1 Vpp, corresponding to a 4-b resolution, under a differential clock of 12 GHz.
Keywords: 10 Gbit/s.; 12 GHz; 14 GHz; 6 GHz; 6 bit; InP DHBT technology; InP-InGaAs-InP.; InP-InGaAs-InP double heterojunction bipolar transistor; Analog-to-digital converter; Clocked track-to-hold transition operation; Digital electronic polarization-mode dispersion compensation circuit; High-speed switched emitter follower; Optical receiver; Total harmonic distortion; Track-and-hold amplifier